PENGARUH MOTIVASI, DISIPLIN KERJA DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI RUMAH SAKIT UMUM DAERAH PURI HUSADA KABUPATEN INDRAGIRI HILIR - jurnalmap map; Ermawita ÔÇÄÔÇÄ; Esa Wahyu Endarti (MAP (Jurnal Manajemen dan Administrasi Publik), 2021)
This study aims to describe the effect of work motivation, work discipline and organizational climate on employee performance at RSUD Puri Husada Indragiri Hilir Regency. This type of research is explanatory research. The population in this study were 218 employees and then taken samples with the formula Slovin obtained a sample of 141 employees as respondents. The results of the study using the t test revealed that the independent variables namely work motivation (X1), work discipline (X2), and organizational climate (X3) partially had a significant effect on teriktat variables namely employee performance (Y) in RSUD Puri Husada, Indragiri Hilir Regency. From the F test results obtained an F count of 19,597 and a significance level of 0,000. Because the F count is 19.597> 2.671 and the significance level is 0.000 <0.05, the hypothesis is accepted. This means that work motivation (X1), work discipline (X2), and organizational climate (X3) together have a significant effect on employee performance (Y) in RSUD Puri Husada, Indragiri Hilir Regency. Keywords: performance, work motivation, work discipline, organizational climate